Anticandidal Properties of Lavandin Essential Oils - Vorobets, Natalia; Yavorska, Halina; Svydenko, Liudmyla (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
The hydrodistillated essential oils of lavandin cultivars (Lavandula hybrid Medic.) Inii and Rabat, which characterized by relatively high amount of monoterpenes were tested for anticandida effects against five pathogenic fungi using in vitro microbial growth inhibition assays; and were compared with that of a commercial antifungal reagent, decasanum and essential oil of Lavandula angustifolia Mill. (lavender oil). The oils of lavandins Inii and Rabat exhibited considerable antifungal activity against all tested Candida spp. Both the tested oils of lavandins Inii and Rabat demonstrated inhibitory action against all the Candida species at low concentrations (100 or 200 µL). The most sensitive were C. pseudotropicalis, C. parapsilosis, and C. kefir, some less sensitive were C. curvata and C. tenuis. However, they were moderately active against Decasanum. The anticandidal effect of essential oil of both lavandins can be due to the interaction of many of their compounds especially linalool, linalyl acetate, camphor, and 1.8-cineole which amount is prevalence. It can be concluded that the oils of lavandins Inii and Rabat have potential against pathogenic Candida pseudotropicalis, C. parapsilosis, C. curvata, C. kefir, and C. tenuis. Essential oils of lavandin cultivars Inii and Rabat are offered for further research as possible alternatives or additional therapeutic agents for candidiasis in diabetics, patients with periodontitis, immune and urogenital system disorders. Particularly promising may be Inii and Rabat essential oils in the treatment of patients with triazole and echinocandin resistant forms of candidiasis.